195k views
0 votes
Witch expression is equivalent to 6^-3

User Yea
by
4.8k points

2 Answers

1 vote

Do you have any options of the equivalent expressions or is it just a plan question that you just asked?



User Stefan Haustein
by
4.8k points
2 votes

For this case we have that by definition of power properties we have to:


a ^ {- b} = \frac {1} {a ^ b}

So, we can write
6 ^(- 3)as an equivalent expression:


6 ^ {-3} = \frac {1} {6 ^ 3}

We know that, by definition:


a ^ nrepresents the multiplication of "a" n times.

So, we have:


6 ^ 3 = 6 * 6 * 6\\6 ^ {- 3} = \frac {1} {6 ^ 3} = \frac {1} {6 * 6 * 6}

Answer:


6 ^ {- 3} = \frac {1} {6 ^ 3} = \frac {1} {6 * 6 * 6}


User Wesley Bland
by
5.6k points